Auxin response factor gene family in Brassica rapa: genomic organization, divergence, expression, and evolution - Mun, Jeong-Hwan (Springer-Verlag, 2012)
Completion of the sequencing of the Brassica rapa genome enabled us to undertake a genome-wide identification and functional study of the gene families related to the morphological diversity and agronomic traits of Brassica crops. In this study, we identified the auxin response factor (ARF) gene family, which is one of the key regulators of auxin-mediated plant growth and development in the B. rapa genome. A total of 31 ARF genes were identified in the genome. Phylogenetic and evolutionary analyses suggest that ARF genes fell into four major classes and were amplified in the B. rapa genome as a result of a recent whole genome triplication after speciation from Arabidopsis thaliana. Despite its recent hexaploid ancestry, B. rapa includes a relatively small number of ARF genes compared with the 23 members in A. thaliana, presumably due to a paralog reduction related to repetitive sequence insertion into promoter and non-coding transcribed region of the genes. Comparative genomic and mRNA sequencing analyses demonstrated that 27 of the 31 BrARF genes were transcriptionally active, and their expression was affected by either auxin treatment or floral development stage, although 4 genes were inactive, suggesting that the generation and pseudogenization of ARF members are likely to be an ongoing process. This study will provide a fundamental basis for the modification and evolution of the gene family after a polyploidy event, as well as a functional study of ARF genes in a polyploidy crop species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00438-012-0718-4) contains supplementary material, which is available to authorized users.